2010
DOI: 10.5114/aoms.2010.14267
|View full text |Cite
|
Sign up to set email alerts
|

Clinical research Tumour necrosis factor gene polymorphisms and migraine in Greek children

Abstract: IntroductionMigraine is considered to be a multifactorial, complex disease. Various genetic and environmental factors contribute to the manifestation of this disease. The aim of this study was to determine whether polymorphisms in the tumour necrosis factor (TNF) region are associated with the risk of migraine. We examined the association between 6 single nucleotide polymorphisms in the coding regions of TNF-α and TNF-β genes and migraine.Material and methodsThe study included two groups of children (group A a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 15 publications
1
28
0
1
Order By: Relevance
“…Two studies suggested an increased risk for migraine (19, 21). Three studies did not suggest an altered risk for migraine for any of the genotypes (14, 17, 22). …”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Two studies suggested an increased risk for migraine (19, 21). Three studies did not suggest an altered risk for migraine for any of the genotypes (14, 17, 22). …”
Section: Resultsmentioning
confidence: 96%
“…After contacting the authors we could obtain complete data for five studies (1822); however, not for two studies (16, 23). We also included genotype and allele frequencies from our previous study (17).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations